The Effect Of Zakat Knowledge and Religiusity on Community Awareness to Paying Zakat for Rice Agriculture (Case Study: Lembah Village, Dolo, Madiun Indonesia) - erfina, Erfinasari (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2021)
The population of Lembah Village, Dolopo District, Madiun Regency is 4,006 people, and 1,023 residents work as farmers, and the area of rice fields is 216 Ha. Seeing the extent of available land shows that zakat's potential in the agricultural sector, especially rice in the region, is quite significant. However, the reality in people's lives, especially in Lembah Village, has not been fully implemented to pay zakat on agriculture. It is due to the lack of public knowledge regarding zakat, especially zakat on rice farming. So far, the management of zakat in this sector has not been entirely appropriately managed. The zakat collected so far has not been submitted to an official institution established by the government. So far, zakat payments for agricultural products are only based on public awareness, and it is not uncommon for those who do not pay zakat for agricultural products. This research focuses on the following problems: 1. How does knowledge of zakat affect public awareness in paying zakat on rice farming in Lembah Village? 2. How does religiosity affect public awareness in paying zakat on rice farming in Lembah Village? 3. How is the effect of knowledge of zakat and religiosity simultaneously on public awareness in paying zakat for rice farming in Lembah Village? The research used is quantitative. The population was 1,023, and the sample consisted of 100 farmers in Lembah Village, Dolopo District, using non-probability sampling techniques through purposive sampling. The data collection technique used a questionnaire, while the data analysis used multiple linear analysis. Based on the results of data analysis conducted by researchers, it can be concluded that: Knowledge of zakat has a significant effect on public awareness with a tcount> t-table,  3.278> 1.660 and multiple linear regression of 0.320. Religiosity has no significant effect on public awareness with the value of tcount> t-table,  1.757> 1.660 and multiple linear regression of 0.217. Knowledge of zakat and religiosity together significantly affects public awareness with the value of f count,  11.688> 3.09 and R Square's value of 0.441.